(untitled) (Al-Qamar, 2020)
According to Islamic ideology, Allah SWT has sent a number of messengers for the guidance of the human race. And Islam is honored to be the full and final religion amongst all the holy scriptures. It is because the religion Islam is believed to be a complete code of life which not only covers detailed teachings regarding personal and individual, but also about collective, social, political, military and ethical aspects of our lives. According to the Islamic principles, a healthy marital relationship in an individual’s life is essential to carry rest matters. This is the reason why the Quran and Hadith quotes at numerous places to maintain a healthy and loving relationship between the two spouses, and emphasis on keeping the holy bond of Nikah intact at every cost. Moreover, the spouses are advised to maintain tolerance, peace and harmony in their lives. Regardless, if the situation between the said parties gets worse, and there seems to be no chance of keeping the contract of Nikah, then the matter could be dealt with Talaq by mutual agreement from both sides. However, this act is considered unpleasant in Shariah or in the eyes of Allah SWT. In the case of necessity, it is the last option available and hence the separation is declared between the parties. Since Talaq is harmful both at individual as well as collective level which in turn incites evil, crime and inferiority complex in the people’s lives, yet still, the rate of divorce has been increasing at an alarming rate in our society. In turn, judicial separation of Nikah Khulʻ, has simultaneously increased in the same proportion. What Khulʻ is? What guidance does Quran ul Hakeem and Sunnah provide us regarding this act? What legal status does rule of Khulʻ occupies in the constitution? This thesis will discuss some more questions including the ones mentioned with detail and in relevance to the same topic.